Comparison of different potassium application methods for maize (Zea mays L.) growth under salt-affected soils - Zaib Un Nisa; Saifullah, Noor ul Ain; Ihsan Ullah, Muhammad; Zia, Zia ullah; Ali, Barkat; Hussain, Zahid; Hussain, Zahid; Hussain, Shahid; Husain, Arif (Journal of Pure and Applied Agriculture, 2023)
Potassium (K) is considered as an important nutrient element for maize growth because its availability varies from different K sources to different soil conditions. Therefore, in this study, a pot experiment was conducted to investigate the efficiency of different K fertilization methods in maize under salt-affected soils. The different application methods (mixing, surface, band placement, and fertigation) were compared by considering the different sources of K, e.g., potassium chloride (KCl) and potassium sulfate (K2SO4). For subsurface application method, the significant increase in shoot fresh weight (SFW) was recorded 272 g and 285 g for KCl, and K2SO4, respectively. For shoot dry weight (SDW), both sources of K either KCl (44.91 g) or K2SO4 (68 g) also showedsignificant results for subsurface application.